European Renal Best Practice Guideline on kidney donor and recipient evaluation and perioperative care - Abramowicz, Daniel; Cochat, Pierre; Claas, Frans H.J.; Heemann, Uwe; Pascual, Julio; Dudley, C.; Harden, Paul; Hourmant, Marivonne; Maggiore, Umberto; Salvadori, Maurizio; Spasovski, Goce; Squifflet, Jean-Paul; et al. (Nephrology, dialysis, transplantation, 2015)
The European Best Practice Guideline group (EBPG) issued guidelines on the evaluation and selection of kidney donor and kidney transplant candidates, as well as post-transplant recipient care, in the year 2000 and 2002. The new European Renal Best Practice board decided in 2009 that these guidelines needed updating. In order to avoid duplication of efforts with kidney disease improving global outcomes, which published in 2009 clinical practice guidelines on the post-transplant care of kidney transplant recipients, we did not address these issues in the present guidelines.The guideline was developed following a rigorous methodological approach: (i) identification of clinical questions, (ii) prioritization of questions, (iii) systematic literature review and critical appraisal of available evidence and (iv) formulation of recommendations and grading according to Grades of Recommendation Assessment, Development, and Evaluation (GRADE). The strength of each recommendation is rated 1 or 2, with 1 being a ‘We recommend’ statement, and 2 being a ‘We suggest’ statement. In addition, each statement is assigned an overall grade for the quality of evidence: A (high), B (moderate), C (low) or D (very low). The guideline makes recommendations for the evaluation of the kidney transplant candidate as well as the potential deceased and living donor, the immunological work-up of kidney donors and recipients and perioperative recipient care.All together, the work group issued 112 statements. There were 51 (45%) recommendations graded ‘1’, 18 (16%) were graded ‘2’ and 43 (38%) statements were not graded. There were 0 (0%) recommendations graded ‘1A’, 15 (13%) were ‘1B’, 19 (17%) ‘1C’ and 17 (15%) ‘1D’. None (0%) were graded ‘2A’, 1 (0.9%) was ‘2B’, 8 (7%) were ‘2C’ and 9 (8%) ‘2D’. Limitations of the evidence, especially the lack of definitive clinical outcome trials, are discussed and suggestions are provided for future research.We present here the complete recommendations about the evaluation of the kidney transplant candidate as well as the potential deceased and living donor, the immunological work-up of kidney donors and recipients and the perioperative recipient care. We hope that this document will help caregivers to improve the quality of care they deliver to patients. The full version with methods, rationale and references is published in Nephrol Dial Transplant (2013) 28: i1-i71; doi: 10.1093/ndt/gft218 and can be downloaded freely from http://www.oxfordjournals.org/our_journals/ndt/era_edta.html.